Vertical Stratification Reduces Microbial Network Complexity and Disrupts Nitrogen Balance in Seasonally Frozen Ground at Qinghai Lake in Tibet - Ni Zhang; Zhiyun Zhou; Yijun Wang; Shijia Zhou; Jing Ma; Jianqing Sun; Kelong Chen (Microorganisms, 2025)
Global climate change has accelerated the reduction of permafrost regions across different altitude gradients, shortening the duration of the freezing period to varying extents. However, the response of the soil microorganisms of frozen soils along altitude gradients remains unclear. In this study, we employed 16S rRNA sequencing and LC-MS metabolomics to investigate the response of soil microbial communities and soil metabolites to vertical stratification in the permafrost soils of the Qinghai Lake region. The results indicated that Proteobacteria, Firmicutes, and Actinobacteria were key soil bacterial phyla in the permafrost soils of Qinghai Lake during the freezing period, with Proteobacteria and Firmicutes showing significant sensitivity to vertical stratification (p < 0.05). The majority of the physicochemical factors exhibited a trend of initially increasing and then decreasing with increasing altitude, whereas pH showed the opposite trend. pH and moisture content were identified as the most important environmental factors influencing soil bacterial community structure. Deterministic processes dominated the assembly of bacterial communities of frozen soils in the Qinghai Lake basin. Co-occurrence network analysis showed that increasing altitude gradients led to a higher average degree of the bacterial network, while reducing network complexity and inter-species connectivity. Soil metabolomics analysis revealed that vertical stratification altered the metabolic profiles of 27 metabolites, with the significantly changed metabolites primarily associated with carbohydrate and amino acid metabolism. In conclusion, the characteristics of the Qinghai Lake permafrost were regulated by regional vertical stratification, which further influenced microbial community structure and soil metabolic characteristics, thereby altering carbon and nitrogen stocks. Specifically, higher altitudes were more favorable for the retention of the carbon and nitrogen stocks of frozen soils in the Qinghai Lake basin.